The interval-parametric synthesis of a linear controller based on the coefficient parameters of robust stability and oscillation; 15th international conference on Sciences and Techniques of Automatic control & computer engineering - STA'2014, Hammamet, Tunisia, December 21-23, 2014 - Gayvoronskiy S. A. Sergey Anatolievich (2014, 2014)
Title screen